1994
DOI: 10.1148/radiology.191.1.8134585
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged mediastinal lymph nodes in bronchogenic carcinoma: assessment with dynamic contrast-enhanced MR imaging. Work in progress.

Abstract: Dynamic contrast-enhanced MR images may provide informative data about the nature of enlarged MLNs in the preoperative assessment of lung carcinoma. Further studies are needed to investigate its usefulness in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…Our results are in accordance with Laissy et al's study [30] of nine patients with bronchogenic carcinomas where a peak enhancement at 60±80 s after contrast injection was found in metastatic mediastinal lymph nodes, with a slow decrease until 6 min. In the same study [30] inflammatory enlarged mediastinal lymph nodes showed a more delayed increase in signal intensity and a lower peak signal intensity compared with metastatic lymph nodes. Gallardo et al [21] recently reported strong and rapid uptake of intravenous contrast in three cases of intramammary lymph nodes with lymphoid hyperplasia.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with Laissy et al's study [30] of nine patients with bronchogenic carcinomas where a peak enhancement at 60±80 s after contrast injection was found in metastatic mediastinal lymph nodes, with a slow decrease until 6 min. In the same study [30] inflammatory enlarged mediastinal lymph nodes showed a more delayed increase in signal intensity and a lower peak signal intensity compared with metastatic lymph nodes. Gallardo et al [21] recently reported strong and rapid uptake of intravenous contrast in three cases of intramammary lymph nodes with lymphoid hyperplasia.…”
Section: Discussionsupporting
confidence: 93%
“…In series comparing CT and MRI, the detection rate of nodal metastases was similar [41, 53, 59]. The hope of increasing sensitivity using dynamic enhanced MRI [60] and MR lymphography [7] has yet not been confirmed. Today, PET-CT is clearly the non-invasive method of choice for lymph node staging in lung cancer.…”
Section: Stagingmentioning
confidence: 99%
“…Therefore, an enlarged node with calcification might be considered to be malignant on MRI but still diagnosed as benign on the basis of CT findings. Furthermore, small clustered LNs on MRI may mimic an enlarged LN due to poor spatial resolution [13,24,33]. However, MRI provides more different planes in longitudinal anatomic evaluation such as the subcarinal and aortopulmonary regions, which are difficult to assess in axial plane [13,21,24,34,35].…”
Section: N-statusmentioning
confidence: 99%